PENENTUAN SUHU DAN WAKTU OPTIMUM PENYEDUHAN BATANG TEH HIJAU (Camelia Sinensis L.) TERHADAP KANDUNGAN ANTIOKSIDAN KAFEIN, TANIN DAN KATEKIN - Nurul Mutmainnah; Sitti Chadijah; Muhammad Qaddafi (Lantanida Journal, 2018)
Tea is one of kind drink that most be preferred and consumed the tea community around the world, even most common of the community utilized tea as a healthy drink because it contains antioxidants. Antioxidants can protect cells from damage that caused by the unstable molecules. The determination of tea temperature and optimum time were aimed to know how the influence of the caffeine content of antioxidants, tannin and chatecine. In a flood expected to contain low caffeine levels with high polyphenols.The method in this research was an extraction method that analyzed by using UV-Vis a spectrophotometer. The results showed that the lowest caffeine level was at a temperature 70°C for 15 minutes of 0.51 %, the highest levels of tannin was at the brewing temperature 70°C for 5 minutes of 4.783 %, the highest cetacean levels were at the brewing temperature 85°C for 5 minutes of 1.14 %. So that, the optimum condition was obtained at the brewing temperature70°C for 5 minutes, which have antioxidant activity about 56.75%.